2021
DOI: 10.1007/s40888-021-00242-8
|View full text |Cite
|
Sign up to set email alerts
|

Imperatives of recognising the complexities: gendered impacts and responses to COVID-19 in India

Abstract: This paper argues that the gendered impact of COVID-19 has both visible and hidden dimensions, and both immediate effects linked with lockdowns and longer-term effects that are likely to emerge sequentially in time and affect recovery. Much of the existing feminist literature on the impact of COVID-19 has neglected these complexities and focused mainly on care work and domestic violence. This has diverted attention away from other key concerns such as livelihood loss, food and nutritional insecurity, indebtedn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…Our results are in line with other findings in the Global South ( SEWA-Bharat, 2020 ; Turner et al, 2021 ). Similar to high-interest loans from moneylenders, sales of assets might push them into more trouble and potentially mark a slide into poverty ( Agarwal, 2021 ; Guha et al, 2021 ; Turner et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results are in line with other findings in the Global South ( SEWA-Bharat, 2020 ; Turner et al, 2021 ). Similar to high-interest loans from moneylenders, sales of assets might push them into more trouble and potentially mark a slide into poverty ( Agarwal, 2021 ; Guha et al, 2021 ; Turner et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, some vendors borrowed from moneylenders at high interest rates, while some sold their durable assets in response to income shocks ( Guha et al, 2021 ; Martínez et al, 2021 ; Turner et al, 2021 ). Consequently, with low repayment capacity and loss of productive assets, they may get into trouble or fall into (deeper) poverty over the long term ( Agarwal, 2021 ; Guha et al, 2021 ; Turner et al, 2021 ).…”
Section: Covid-19 Social Distancing and Street Vendors: An Analytical...mentioning
confidence: 99%
“…Recent research has shown that women are disproportionately impacted by health and economic crises in various ways, including food security and nutrition, access to health facilities, services, and economic opportunities, and gender-based violence [ 19 ]. In addition, numerous studies have shown that the COVID-19 epidemic had a more significant impact on women than men [ 20 , 21 , 22 , 23 , 24 ]. While fatality rates are higher for men globally, the crisis’s socio-economic effects are particularly severe for women [ 19 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…The health consequences and economic impact have strained systems and further exacerbated the frailties of developing countries. Multiple studies have been carried out on the effects of COVID-19: its origins, economic impact, weaknesses of healthcare systems around the world and the differential effects on men and women's health and career progression (Agarwal, 2021a(Agarwal, , 2021b. Since explicit data from specific countries are still very limited, reliable comparisons are difficult to undertake.…”
Section: Introductionmentioning
confidence: 99%